Penerapan Model MIMIC untuk Menguji Konsistensi Hasil Pengukuran melalui Skala - Wahyu Widhiarso (Journal of Education and Learning (EduLearn), 2012)
This study aimed to demonstrate the use of multiple indicators and multiple (MIMIC) model in testing the consistency of the measurement results when it's applied to individuals with different characteristics. Self-Esteem and Student Motivation Scale were employed to measure participant attributes. Impact of three student characteristics (gender, intelligence and school location) on both measurement model were examined. Total of 2981 students from 30 cities of 15 provinces were participated in this study. Data analysis was utilized using confirmatory factor analysis under structural equation modeling (SEM) approach. Results showed that measuring self-esteem was prone to be contaminated by individual heterogeneity. However, contrary results was found on motivation measure. Excluding three student characteristics as covariance in the model have increased model fit indices in the self-esteem measurement model, but not in the self-esteem. The presence of susceptibility scale to different characteristics indicated that this scale needs to be further modified. Therefore, when it is applied to heterogeneous population, the measurement results will produce consistently results.